(untitled) (Research Nepal Journal of Development Studies, 2022)
Good governance is a vital part of the governing system based on conscious oriented and meaningful participation, followed by a legal system that is effective and efficient service delivery, accountable, transparent, responsive, equitable, and more inclusive. This study tries to explore the practice and policy of good governance in Rajapur Municipality. The theoretical underpinnings for the study are based on descriptive research design. The respondents are selected by purposive and convenience sampling methods. The interview and questionnaire were the main tools for gathering the required information. The study disclosed a low level of accountability and transparency in the Rajapur municipality. It is a case study of Rajapur Municipality. In conclusion, the current good governance practice of Rajapur Municipality is weak and identified with a high level of rent-seeking among public servants as well as appointed and elected authorities. This research claims for the existence of governance which guarantees public appointment in decision making and prioritization of shared problems, accompanied by the transparent and accountable government are recommendable